Effect of MIG Welding Parameters on the Mechanical Properties of AISI 304 Austenitic Stainless Steels - Amjed M. Jebbur; Salah S. Abed AlKareem; Faiz F. Mustafa (Al-Khawarizmi Engineering Journal, 2022)
The present research  investigates joints welding of 304L austenitic stainless steel using metal inert gas (MIG) welding method. The research explores the effect of process parameters (arc voltage, wire feed rate, and electrode wire diameter) on the mechanical properties of stainless steel.  The above variables are varied  respectively with 18.5, 19, 19.5 V, 116, 127, 137 mm/s, and 0.8, 1, 1.2 mm, with E308L as a filler electrode. The design matrix of the experiments was determined using the design of experiment (DOE) program Minitab 17 based on the levels of input elements used. The Taguchi orthogonal matrix methodology (Taguchi) technique was used to develop some empirical analysis for the maximum tensile strength and proper surface hardness as a function of the welding parameters mentioned above. The ( ) analysis was used to statistically verify the model's adequacy. The results show that the wire feed rate had  the greatest effect on the tensile strength of the welded joints when choosing the medium level of arc voltage (19 V), while the arc voltage had a substantial influence on the micro-hardness of all welded joints. The weld-joint zone is given a higher micro-hardness value compared to the base metal zone.